2021
DOI: 10.3390/jcm10040703
|View full text |Cite
|
Sign up to set email alerts
|

Ovulatory-Based FET Cycles May Achieve Higher Pregnancy Rates in the General Population and among Anovulatory Women

Abstract: This study evaluated which endometrial preparation protocol in frozen embryo transfer (FET) cycles provides the best results for polycystic ovarian syndrome (PCOS) patients and the general population. This retrospective study of 634 FET cycles was conducted 2016–2018. Cycles were divided into Group A: Artificial endometrial preparations for FET (aFET; n = 348), Group B: Ovulatory cycle (n = 286) to compare two methods of endometrial preparation for FET. Artificial endometrial preparation with exogenous estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…In addition, the authors mentioned that in their country, letrozole was primary prescribed to patients with unexplained infertility rather than PCOS patients. To corroborate the findings of Tatsumi et al, a more recent retrospective cohort study conducted in Israel concluded that ovulation induction using letrozole might induce normal ovulation and physiological FET, resulting in better pregnancy rates in FET treatments for PCOS patients [ 26 ]. A recent historical cohort analysis on women with PCOS found that ovarian stimulation (OS) protocol with low doses of HMG achieved a higher LBR than hormone replacement therapy (HRT) protocol accompanied by the poorest endometrial thickness [ 27 ].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the authors mentioned that in their country, letrozole was primary prescribed to patients with unexplained infertility rather than PCOS patients. To corroborate the findings of Tatsumi et al, a more recent retrospective cohort study conducted in Israel concluded that ovulation induction using letrozole might induce normal ovulation and physiological FET, resulting in better pregnancy rates in FET treatments for PCOS patients [ 26 ]. A recent historical cohort analysis on women with PCOS found that ovarian stimulation (OS) protocol with low doses of HMG achieved a higher LBR than hormone replacement therapy (HRT) protocol accompanied by the poorest endometrial thickness [ 27 ].…”
Section: Discussionmentioning
confidence: 80%
“…1 . Based on sensitivity analysis, 1 study (Aslih 2021) [ 14 ] was found with publication bias (Supplementary Fig. 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis including 4 retrospective studies with 2933 women with PCOS published from 2013 to 2019, suggested that the pregnancy outcomes, including rates of live birth, ongoing pregnancy, clinical pregnancy, implantation and miscarriage rate were not significantly different between artificial and ovarian stimulation cycles [ 12 ]. After that, 1 RCT study [ 13 ] and 4 retrospective studies [ 14 17 ] on the topic have been published, suggesting the therapeutic effects might be different among various ovulation stimulation regimens. Which stimulation regimen superior to HRT has yet been analyzed in the previous review paper.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we also observed that the rate for the presence of a corpus luteum (because of different endometrial preparation protocols for FET) in PCOS phenotypes A and D was significantly lower than that in controls, which might be another reason for the higher rate of abortion. In clinical practice, for PCOS women with OA, clinicians generally adopt a hormone replacement therapy (HRT) cycle to prepared the endometrium for FET 29 . Recently, Xu et al 30 noticed that HRT cycles were related to a higher abortion rate, which is consistent with the results of a prior study 31 .…”
Section: Discussionmentioning
confidence: 99%